Pemberdayaan Wakaf Uang Sebagai Upaya Peningkatan Kesejahteraan Masyarakat - Moh. Ah. Subhan ZA (Universitas Islam Lamongan, 2017)
Waqf is a form of worship that has a high sense of solidarity towards human beings. Its existence has greatly helped the development of proselytizing in Islamic countries. But, in the implementation of the waqf is limited only in the construction of worship and education places. This is because the understanding of most people who say that waqf can only be done with immovable property such as land. Whereas on the other hand, there are other ways of waqf that has far more great benefit than immovable object, that is waqf of money. The waqf of money is a strategic step to improve the welfare of the community by investing in Islamic financial institutions with the principle of profit sharing (mudharabah and musyarakah), rent (Ijarah), murabahah or by opening a business. The results of the management of money waqf are then used for social purposes such as to improve Islamic education, Islamic hospital construction, assistance of economic empowerment of the community as well as the aid of religious facilities and infrastructure. After understanding the great potential of the money waqf, it is necessary for us to do. First, we must change the understanding of the waqf conception that has been believed by the Indonesia community up till now that waqf is limited to the immovable endowments. Second, the socialization on existence of waqf money along with its concept to society is has to be done. Third, the certificate of money waqf should not be with a large nominal value. There should be at least a fraction of 20,000, 10,000 or even 5000, so that community participating in this money of waqf becomes more. Fourth, the benefits of productive endeavor of the waqf fund should be immediately channeled to the eligible community as it relates to the belief of waqif and so that the community knows about the benefits of the money waqf soon. Fifth, the disbursement of profit to the poor should not only be money, but also a business that can elevate their economy. Sixth, management of money waqf should not only be in sharia financial institutions, but also in the community such as mosques, madrasah or non-governmental organizations. In this way, it will facilitate the scope of the community and can increase the amount of community participation in waqf. Keywords: Money Waqf, Cash Waqf, Community Prosperity